Penurunan Kadar Kolesterol Total pada Pasien Hipertensi yang Mendapat Terapi Bekam di Klinik An-Nahl Purwokerto - Saryono (Jurnal Keperawatan Soedirman, 2010)
Hypertension is abnormality condition that one of caused by hypercholesterolemia. Hypertension curing has bad side effects until death. The other choice to solve this problem is cupping therapy. The objectives of this study is to obtain an information on cupping therapy effect to blood total cholesterol level. This study used pre experimental study with one-group pre-post test design without control group. Purposive sampling was applied to choose a sample. Data analysis used paired t test. The average of total cholesterol level before and after cupping therapy were 204,93 and 187,53 respectively. T-test analysis for the effect cupping therapy to total cholesterol level was 4,01 (p= 0,0001). Therefore, p value less than ? (5%) which mean cupping therapy have an effect to decrease the total cholesterol level. The cupping therapy was decreased to total cholesterol level for hypertension patient in An-Nahl Clinic of Purwokerto.